Analyses of synthetic N-acyl dopamine derivatives revealing different structural requirements for their anti-inflammatory and transient-receptor-potential-channel-of-the-vanilloid-receptor-subfamily-subtype-1 (TRPV1)-activating properties - Pallavi, Prama; Pretze, Marc; Li, Yingchun; Hofmann, Björn Bastian; Stamellou, Eleni; Wängler, Carmen; Wängler, Björn; Mörz, Handan; Binzen, Uta; Greffrath, Wolfgang; Treede, Rolf-Detlef; Krämer, Bernhard; et al. (Journal of medicinal chemistry, 2018)
We studied the chemical entities within N-octanoyl dopamine (NOD) responsible for the activation of transient-receptor-potential channels of the vanilloid-receptor subtype 1 (TRPV1) and inhibition of inflammation. The potency of NOD in activating TRPV1 was significantly higher compared with those of variants in which the ortho-dihydroxy groups were acetylated, one of the hydroxy groups was omitted (N-octanoyl tyramine), or the ester functionality consisted of a bulky fatty acid (N-pivaloyl dopamine). Shortening of the amide linker (ΔNOD) slightly increased its potency, which was further increased when the carbonyl and amide groups (ΔNODR) were interchanged. With the exception of ΔNOD, the presence of an intact catechol structure was obligatory for the inhibition of VCAM-1 and the induction of HO-1 expression. Because TRPV1 activation and the inhibition of inflammation by N-acyl dopamines require different structural entities, our findings provide a framework for the rational design of TRPV1 agonists with improved anti-inflammatory properties.